A Note on "Data mining based noise diagnosis and fuzzy filter design for image processing". (January 2016) - Jindal, Khushneet; Kumar, Rajiv
Abstract: Wang et al. (2014) developed a data mining approach for noise type diagnosis and proposed a fuzzy filter design for enhancing the quality of noise corrupted images. The aim of this note is to point out that this approach can be used only if all the feature parameters are non-negative and cannot be used if some of the features parameters are negative.